Reasons for clozapine discontinuation in patients with treatment-resistant schizophrenia - (:unkn) unknown (ELSEVIER IRELAND LTD, 2019)
Although clozapine is more effective than other antipsychotics in the treatment of schizophrenia, the rate of its discontinuation is also high. The aim of this retrospective chart-review study was to investigate the causes of clozapine discontinuation in patients with treatment-resistant schizophrenia. This study included a total of 396 patients with schizophrenia, 240 still on clozapine therapy and 156 who discontinued clozapine, and compared their clinical characteristics. Those who discontinued clozapine had a longer history of illness and more hospitalizations before clozapine and tended to be older. Inadequate response was more common among clozapine discontinuers compared to continuers. The most common reason for discontinuation was the side-effects associated with clozapine (49%). Discontinuation from patient decision or by the psychiatrist due to noncompliance was the second (29.7%) and discontinuation due to lack of efficacy was the third most frequent reason (21.3%). The patients who discontinued clozapine because of cardiac side effects were younger, had shorter duration of clozapine use, and had lower maximum clozapine dose compared to the other discontinuers. Our findings point out the importance of enhancing psychiatrists' ability to handle manageable side effects to minimize discontinuations and maximize the benefits of clozapine in patients with treatment-resistant schizophrenia.
Keywords: CLINICAL-PRACTICE; ANTIPSYCHOTICS; GUIDELINES; ADHERENCE